PERIOD BEFORE WEED INTERFERENCE IN TRANSGENIC SOYBEAN - BENEDETTI, José Guilherme Rehder; PEREIRA, Larissa; ALVES, Pedro Luís da Costa Aguiar; YAMAUTI, Micheli Satomi (Scientia Agraria, 2009)
The experiment was carried out to determine the period before weed interference in soybean cv. Monsoy 7908 RR in a conventional till system. The periods of weed control studied were: 0, 10, 15, 20, 30, 40, 50, 60 and 118 days after planting, totaling 10 treatments, arranged in a randomized block design, with four replications. The weed community comprised twenty species. The species Alternanthera tenella, Digitaria nuda and Eleusine indica were the most prominent. Soybean grew along with the weed community up to 25 days after planting, without significant yield loss. Weed interference during the full crop cycle reduced, in average, 30% of potential productivity.